EMPLOYING THE HYBRID ORGANIZATION MODEL TO ACHIEVE STRATEGIC AUTHENTICITY THROUGH THE MEDIATING ROLE OF STRATEGIC ADAPTATION VARIABLE - Salman, M.M. Noor Samir; Mullan, M.M. Nasser Sami (PT. Antis International Publisher, 2026)
Objective: This study examines how hybrid organizational models contribute to achieving strategic authenticity within Iraq’s private higher education sector, with a particular focus on institutions in Dhi Qar Governorate. Method: Using institutional and organizational theory as the framework, the study employed a questionnaire distributed to 200 deans, associate deans, and department heads across private universities and colleges. Structural equation modeling (SEM) and confirmatory factor analysis were conducted to assess the relationships among hybrid organizational logics, authenticity, strategic adaptation, and organizational performance, confirming strong construct validity. Results: Findings indicate that hybrid logics are moderately embedded within private institutions, yet authenticity and strategic adaptation remain underdeveloped, limiting their positive influence on performance. Notably, strategic adaptation emerged as a significant mechanism that enables institutions to balance academic integrity with market demands. Novelty: This research extends organizational theory by demonstrating the applicability of hybrid organizational models in conflict-prone higher education systems and highlights the need for value-based leadership and adaptive governance to enhance legitimacy, flexibility, and sustainability within Iraq’s volatile private higher education environment.